Enhanced fracture fixation stability and osseointegration through over-compression: Design of an annular compression plate for posterolateral tibial plateau fractures - Chao-Wei Huang; Xin-Cheng Dai; Yu-Tzu Wang (Materials & Design)
Posterolateral tibial plateau fractures (PTPF) fixation is challenged by fragment instability and insufficient biomechanical consideration, leading to joint surface incongruity and impaired fracture healing. This study developed an annular compression plate (AC plate) to enhance bone interface compression and fixation stability in PTPF. The AC plate features an annular enclosure to prevent fragment collapse and a 1° over-compression angle at primary bending angles to promote osseointegration. The AC plate was bent by stamping, and its spring-back was compensated through the die design to minimize bending errors. Finite element analysis was utilized to evaluate the AC plate’s pressurization capability, spring-back compensation and biomechanical behavior in PTPF reconstruction. The static fixation stability test and dynamic biomechanical test were conducted to compare the AC plate and the commercial locking compression plate. The stamping spring-back compensation analysis suggested that adjusting die bending angles could reduce compensation deviation to 3.39%–4.82% and ensure precise plate conformation to the tibial plateau. Pressurization capability analysis revealed that the AC plate maintained a 33.4% contact area at the bone interface. Furthermore, biomechanical analysis showed that the AC plate generated a minimum interfacial strain of 2192.7 μ, which contributed to stable fixation and enhanced osseointegration. These findings indicate that the AC plate delivers stable compression, promotes osseointegration, and provides superior mechanical support, thereby improving outcomes in PTPF reconstruction.